University of the Philippines Institute of Library Science - Integrated Set of Information Sytems (UPILS-ISIS) - Reside, Marie Desiree H. (Institute of Library Science, University of the Philippines Diliman, 2002)
The University of the Philippines Main Library started to automate its card catalog using CDS/ISIS in 1986. CDS/ISIS was distributed to the other unit libraries on the same year, which the Institute of Library Science (ILS) Library is a part. The ILS Library began to use WINISIS version 1.3 since its release in 1999. Its CDS/ISIS database was imported to use WINISIS.